Effects of Temperature on the Expression of Two Ovarian Differentiation-Related Genes foxl2 and cyp19a1a - Shen, Zhi-Gang; Eissa, Nour; Yao, Hong; Xie, Zhi-Gang; Wang, Han-Ping (Frontiers in Physiology, 2018)
Exposure to stress induces a series of response and influences a wide range of biological processes including sex differentiation in fish. The present work investigated the molecular and physiological response to thermal stress throughout the early development stage covering the whole period of sex differentiation of bluegill, Lepomis macrochirus. Larvae were treated using three temperatures, 17, 24, and 32 °C from 6 to 90 days post-hatching (dph) in 30 L round tanks. There is no significant difference of sex ratio and survival among the three temperature groups in the geographic population used in this study. Two ovarian differentiation-related genes foxl2 and cyp19a1a were detected at 7 dph suggesting that these genes have already played a role prior to sex differentiation. The expression of foxl2 reached the peak and was thermo-sensitive just prior to the onset of ovarian differentiation at 27 dph. Histological examination displayed that proliferation of germ cells and ovarian differentiation were delayed at the low temperature treatment (17°C) at 97 dph compared to higher temperatures. In conclusion, the water temperature regulates the sex differentiation of bluegill through modulation of the expression of foxl2 and cyp19a1a. A comparative study of the expression profile of sex differentiation related genes in species will shed light on the evolution of sex determination mechanisms and the impact of stress on sex differentiation.